2003
DOI: 10.1177/002215540305101201
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of the Low-density Lipoprotein Receptor-related Protein-1 (LRP-1) in Rats with Prostate Cancer

Abstract: S U M M A R YThe aim of this work was to evaluate by immunohistochemistry (IHC) the expression of both LRP-1 and urokinase-type plasminogen activator receptor (uPAR) at different developmental stages of rat prostate disease by using a prostate cancer model previously developed in our laboratory. We found that LRP-1 was weakly expressed in normal prostates and in rats with hyperplastic glands. The expression of this receptor increased and correlated with the degree of premalignant lesions (PIN I, II, and III). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…Our study showed decreased expression of LRP1 in cell lines derived from non-small lung, prostate and colon carcinoma, all consistent with results described in literature [13,52,53]. The here first described ubiquitous expression of smLRP1 in tumour cell lines of different origins as well as human tissues (Fig 3A and 3B) extents our knowledge about LRP1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed decreased expression of LRP1 in cell lines derived from non-small lung, prostate and colon carcinoma, all consistent with results described in literature [13,52,53]. The here first described ubiquitous expression of smLRP1 in tumour cell lines of different origins as well as human tissues (Fig 3A and 3B) extents our knowledge about LRP1.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing tumour cells and corresponding healthy tissues showed differences in expression of smLRP1 and LRP1 (Fig 4A and 4B). LRP1 expression was decreased in cell lines derived from non-small lung, prostate, and colon carcinoma as described in literature [13,52,53]. Variations in LRP1 expression might be due to varying cell density at time of harvesting the cells [54].…”
Section: Discussionmentioning
confidence: 91%
“…For proliferation index and apoptosis index, the percentages of proliferating tenoblasts and apoptotic tenoblasts in all tenoblasts were calculated and the same was done for tenocytes. For the evaluation of protein expression in tenocytes and tenoblasts, an adapted scoring scheme was used (no detectable expression ϭ 0; detectable expression with the percentage of positive cells less than 10% ϭ 1; significant expression with the percentage of positive cells much higher than 10% ϭ 2) (Gilardoni et al 2003), and the results were presented as median scores. Because a paired comparison was employed, detectable expression in score 1 and significant expression in score 2 also referred to a direct comparison in staining intensity, i.e., if an obvious difference in staining intensity between elongated tendon cells and ovoid tendon cells was consistently noted, the higher staining intensity was scored 2 and the lower staining intensity was scored 1, even when the percentages of positive cells were similar.…”
Section: Image Analysismentioning
confidence: 99%
“…Lipoprotein receptor related-protein 1 has already been attributed a role in cancer shortly after its discovery in 1988 ( Herz et al, 1988 ). Initially, several groups reported decreased LRP1 expression (Figure 1C ) levels in various cancer cell lines and tissues, thus assigning a tumor suppressive role to this receptor ( Kancha et al, 1994 ; de Vries et al, 1996 ; Gilardoni et al, 2003 ). These findings provided a rationale for earlier studies in which decreased binding and uptake of α 2 -macroglobulin (α 2 M), an LRP1 ligand, were observed in multiple cancer cell lines ( Van Leuven et al, 1979 ; Saksela et al, 1981 , 1984 ; Jensen et al, 1989 ).…”
Section: Lrp1 and Cancer: A Long But Difficult Marriagementioning
confidence: 99%